The Study on Water Balance in Mlech Reservoir Under Climate Change Effects, Kampot Province - Ramy Lun; Amret Chham; Sophos Chea; Vichhainin Khem; Kunavath Ou; Sovithia Samreth (Indonesian Society of Limnology, 2022)
The Mlech Water Treatment Plant (WTP) has produced 2,000 m3/day of drinking water using raw water from Mlech, Kampot province. Since water demand would be increased in the future, so that the extension water treatment capacity will be the main challenges in correspondence with the development of planning of PPWSA. The water balance estimation is also the critical point in order to make a good decision on extension WTP at existing area. Therefore, the objectives of this study aimed to analyse the water balance in Mlech reservoir by using data from 2002 to 2011, in 2030s and in 2050s. The Rational Method was applied for estimating the streamflow into the reservoir. Water balance was computed following hydrological concept. SWAT and HEC-HMS models were performed to predict the future streamflow. The future climatic data were projected from 2012 to 2050 under climate change scenario RCP 4.5 with three general circulation models (GCMs) including IPSL-CM5A-MR, GISS-E2-R-CC and GFDL-CM3. As a result, the water balance remains about 11.40 Mm3/year in reservoir in baseline. In 2030s, the water quantity will be approximately 58.70 Mm3/year, 62.09 Mm3/year and 59.58 Mm3/year under model IPSL-CM5A-MR, GISS-E2-R-CC and GFDL-CM3, respectively. In addition, the water quantity will be slightly changed in 2050s comparing to 2030s. According to the scenario of extension WTP capacity, this study found that the water flow into downstream will be decreased to 37.14 Mm3/year to 33.84 Mm3/year when WTP’s capacity increased from 2,000 m3/day to 14,000 m3/day,respectively. Furthermore, the volume of water overflow to downstream for irrigation uses is 30.32 Mm3/year when WTP’s capacity increased to 12,000 m3/day in 2050s. Irrigation water need is about 28.00 Mm3/year. In recommendation, the total WTP’s capacity should be extended from 2,000 m3/day to 10,000m3/day from Mlech reservoir based on the future water demand.